Ar preskriptyvizmas veikia? Taisomi žodžiai Lietuvos radijo ir TV eteryje 1960–2010 - Nevinskaitė, Laima; Tamaševičius, Giedrius (Taikomoji kalbotyra, 2019)
This special issue includes a study of the effects of prescriptivism on the speech of Lithuanian radio and television in the period between 1960 and 2010. The investigation is corpus-based and focuses on the use of lexical items that are classified as “incorrect” by the Lithuanian norm-setters. Editor of the special issue: Loreta Vaicekauskienė